Neoadjuvant Radiotherapy: Changing the Treatment Sequence to Allow Immediate Free Autologous Breast Reconstruction - Hughes, Kimberley; Neoh, Derek (Journal of Reconstructive Microsurgery, 2018)
Background Locally advanced breast cancer (LABC) is traditionally treated with a multimodal approach of chemotherapy, surgery, and postmastectomy radiotherapy (PMRT). The advantages of immediate breast reconstruction (IBR) are well described and include improved aesthetic outcomes, fewer surgical procedures, shorter treatment period, and a higher quality of life. However, this sequence makes immediate free autologous reconstruction more challenging as PMRT can have deleterious and unpredictable effects on the flap. We have reversed this treatment sequence with neoadjuvant chemotherapy and radiotherapy, followed by mastectomy and immediate free autologous reconstruction. To our knowledge, this is the first series to assess the outcomes of neoadjuvant radiotherapy on immediate free microvascular breast reconstruction.Methods A review of patients with LABC who underwent immediate free autologous breast reconstruction post neoadjuvant chemoradiotherapy between 2013 and 2017 was conducted. All reconstructions were performed by a single reconstructive team. The primary end points were flap failure and surgical complications. Secondary end points were pathological response rate and disease recurrence.Results A total of 40 women with an average age of 48.1 (36–61) and average body mass index of 25.6 (18–37) were included. The most common choice of flap was immediate deep inferior epigastric perforator (DIEP, 31), followed by transverse or diagonal upper gracilis (5), muscle-sparing transversus abdominis (3), and stacked DIEP (1). Our major complication rate was 12.5% and minor complication 15%. There were no cases of local recurrence and only three cases (7.5%) of distant disease progression.Conclusion From our experience, this treatment sequence allows patients to have an immediate gold standard reconstruction without an increase in surgical morbidity. It affords the benefits of IBR without concern in delaying adjuvant therapy and appears to be safe from an oncological perspective.
Keywords: autologous breast reconstruction; neoadjuvant radiotherapy; locally advanced breast cancer